Regulation of UGT1A1 and HNF1 transcription factor gene expression by DNA methylation in colon cancer cells - Bélanger, Anne-Sophie (BioMed Central, 2010)
BACKGROUND: UDP-glucuronosyltransferase 1A1 (UGT1A1) is a pivotal enzyme involved in metabolism of SN-38, the active metabolite of irinotecan commonly used to treat metastatic colorectal cancer. We previously demonstrated aberrant methylation of specific CpG dinucleotides in UGT1A1-negative cells, and revealed that methylation state of the UGT1A1 5'-flanking sequence is negatively correlated with gene transcription. Interestingly, one of these CpG dinucleotides (CpG -4) is found close to a HNF1 response element (HRE), known to be involved in activation of UGT1A1 gene expression, and within an upstream stimulating factor (USF) binding site. RESULTS: Gel retardation assays revealed that methylation of CpG-4 directly affect the interaction of USF1/2 with its cognate sequence without altering the binding for HNF1-alpha. Luciferase assays sustained a role for USF1/2 and HNF1-alpha in UGT1A1 regulation in colon cancer cells. Based on the differential expression profiles of HNF1A gene in colon cell lines, we also assessed whether methylation affects its expression. In agreement with the presence of CpG islands in the HNF1A promoter, treatments of UGT1A1-negative HCT116 colon cancer cells with a DNA methyltransferase inhibitor restore HNF1A gene expression, as observed for UGT1A1. CONCLUSIONS: This study reveals that basal UGT1A1 expression in colon cells is positively regulated by HNF1-alpha and USF, and negatively regulated by DNA methylation. Besides, DNA methylation of HNF1A could also play an important role in regulating additional cellular drug metabolism and transporter pathways. This process may contribute to determine local inactivation of drugs such as the anticancer agent SN-38 by glucuronidation and define tumoral response.